Perilaku Masyarakat terhadap Kejadian DBD di Kecamatan Ciracas Jakarta Timur - Rojali Rojali; Awan Putri Amalia (Jurnal Kesehatan Manarang, 2020)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus and is transmitted by mosquitoes Aedes aegypti and Aedes albopictus. This study is an analytical study with a cross sectional approach with the title "Factors Influencing Community Behavior Against Dengue Hemorrhagic Fever in RW 06 Ciracas Village, Ciracas Subdistrict, East Jakarta in 2019", aiming to determine the relationship between individual characteristics, behavior, and environment for dengue incidence. Data collection is done by interviews and observations using questionnaires and observation sheets. Data were analyzed by univariate and bivariate methods with chi-square analysis. The number of samples in this study were 107 people with the sample technique used was simple random sampling. The results showed that 15.9% of the people were suffering from dengue fever in the last 6 months. Of the 10 variables there are 4 variables that have a relationship to the incidence of DHF, namely age (p-value = 0,000), gender (p-value = 0.017, OR = 4.146), knowledge (p-value = 0.034, OR = 5,231), action (p-value = 0.045, OR = 3.740), while education (p-value = 0.086), work (p-value = 0.748), attitude (p-value = 0.078), the existence of larvae (p-value = 0.716) has no relationship to the incidence of DHF and 1 variable that cannot be connected is the existence of a water reservoir because 100% has a water reservoir and 1 variable only looks at the picture of dengue incidence based on season.